2013
DOI: 10.1073/pnas.1221509110
|View full text |Cite
|
Sign up to set email alerts
|

Identifying host species driving transmission of schistosomiasis japonica, a multihost parasite system, in China

Abstract: Understanding disease transmission dynamics in multihost parasite systems is a research priority for control and potential elimination of many infectious diseases. In China, despite decades of multifaceted control efforts against schistosomiasis, the indirectly transmitted helminth Schistosoma japonicum remains endemic, partly because of the presence of zoonotic reservoirs. We used mathematical modeling and conceptual frameworks of multihost transmission ecology to assess the relative importance of various def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 32 publications
3
118
0
1
Order By: Relevance
“…For example, Rudge et al . (10) quantified host species contributions to the number of cases generated ( R 0 ) of S. japonicum in China, for which more than 120 host species have been identified. They showed that bovids maintain infection in marshlands, whereas rodents are the main source of transmission in hilly areas, which suggests that different control strategies are needed in the two habitats.…”
Section: Approaches For Understanding Multilevel Infection Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Rudge et al . (10) quantified host species contributions to the number of cases generated ( R 0 ) of S. japonicum in China, for which more than 120 host species have been identified. They showed that bovids maintain infection in marshlands, whereas rodents are the main source of transmission in hilly areas, which suggests that different control strategies are needed in the two habitats.…”
Section: Approaches For Understanding Multilevel Infection Processesmentioning
confidence: 99%
“…1), such that treating animals to reduce their worm burdens improves individual survival but, by enabling infected hosts to live longer, is predicted to increase population-level spread of bTB (63). Reciprocally, variation in host community composition within a region can affect infection risk and spread at the individual and population levels (10, 55). For vector-borne infections such as Lyme disease, wildlife species vary considerably in their tendency to amplify the bacterium responsible and transmit it to suitable tick vectors, such that regional variation in host species diversity is hypothesized to be a major determinant of local infection risk for humans (65) (Box 1).…”
Section: Approaches For Understanding Multilevel Infection Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…vaccine stockpiling.[113]molecular techniques such as whole genome sequencing can for some diseases be used to trace transmission events.[114]7. which transmission pathway or group is driving transmission, and therefore where should interventions be targeted?mathematical models of disease dynamics, informed by many of the above forms of study, can be used to identify key and maintenance hosts, and also to predict the impact of interventions.[6,10,115117]…”
Section: Disentangling and Quantifying Transmissionmentioning
confidence: 99%